2019
DOI: 10.14309/01.ajg.0000592144.29288.25
|View full text |Cite
|
Sign up to set email alerts
|

652 Ustekinumab Intravenous Reinduction Therapy Is Effective at Recapturing Response in Patients With Crohn's Disease

Abstract: INTRODUCTION: Ustekinumab is a monoclonal antibody used in the treatment of Crohn's Disease that acts as an antagonist to interleukin-12 and interleukin-23. It is administered as a single intravenous infusion followed by subcutaneous maintenance dosing. There is paucity of literature evaluating the efficacy of repeating an intravenous infusion to recapture response among patients experiencing secondary loss of response to ustekinumab. We report on a cohort of patients who received a second intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…After removing duplicates and preliminary screening, 94 studies were assessed for eligibility. Eighty studies were excluded (see Figure 1 and Table S3 for details), and 14 studies were included in the meta‐analysis 5,21‐33 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removing duplicates and preliminary screening, 94 studies were assessed for eligibility. Eighty studies were excluded (see Figure 1 and Table S3 for details), and 14 studies were included in the meta‐analysis 5,21‐33 …”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Tables 1 and S4. Eight studies were full‐text articles, 5,22,25,26,29,30,32,33 and six were conference abstracts 21,23,24,27,28,31 . Three studies were multicentre randomised controlled trials, 5,24,31 and the remaining 11 were retrospective cohort studies (six multicentres and five single centres) 21‐23,25‐30,32,33 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations